When the Sea is Uncertain: Why Are Fishermen Reluctant to Start Businesses on Lowita Beach, While Non-Coastal Communities Benefit from It? - Nirmasari, Dian; Nur, Yustika; Salida, Amrizal; Amin, Gazali (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
This study aims to explore why fishermen's involvement in entrepreneurship in coastal areas remains low and why most businesses are instead managed by non-coastal communities, even though entrepreneurship can improve welfare and economic independence for coastal families especially when weather conditions prevent fishermen from going to sea. The study uses a descriptive qualitative method with an exploratory approach to analyze fishermen's engagement in entrepreneurship at Lowita Beach. Data collection techniques include observation, documentation, and semi-structured interviews with selected informants. The research informants consisted of fishermen as key informants, fishing groups, and government representatives as supporting informants, selected through accidental sampling due to the fact that not all individuals were willing to be interviewed. Data analysis follows the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing, supported by NVivo software to facilitate the analysis process. To ensure data validity, the study applies triangulation of techniques, sources, and time to strengthen the credibility and reliability of the findings. The results show that the low involvement of fishermen in entrepreneurship at Lowita Beach is driven by a complex set of factors that go beyond limited capital. Generational traditions have shaped fishing as a primary social identity, causing land-based businesses to be seen as less desirable. Low levels of education and financial literacy also make it difficult for fishermen to manage businesses, while gender norms restrict women's ability to contribute economically. In addition, past business failures have created a collective trauma that reinforces the fear of starting new ventures. In contrast, non-coastal communities tend to dominate local businesses because they possess stronger capital, experience, literacy, and social networks. To increase fishermen's participation, the study proposes strategies such as continuous training and mentoring, access to group-based microfinance, institutional strengthening, household business diversification through processed marine products, and multi-actor collaboration. Thus, empowering fishermen in coastal entrepreneurship must be viewed as a comprehensive process that integrates cultural, social, economic, and institutional dimensions.